2016
DOI: 10.1021/acsmedchemlett.6b00062
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Tesirine, a Clinical Antibody–Drug Conjugate Pyrrolobenzodiazepine Dimer Payload

Abstract: Pyrrolobenzodiazepine dimers are an emerging class of warhead in the field of antibody-drug conjugates (ADCs). Tesirine (SG3249) was designed to combine potent antitumor activity with desirable physicochemical properties such as favorable hydrophobicity and improved conjugation characteristics. One of the reactive imines was capped with a cathepsin B-cleavable valine-alanine linker. A robust synthetic route was developed to allow the production of tesirine on clinical scale, employing a flexible, convergent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 26 publications
2
132
0
1
Order By: Relevance
“…However, the activity of cytotoxics can be context dependent, where certain classes of drugs are more effective than others depending on the type of cancer. Therefore, studies were conducted to determine the relative activity of 5T4-Tub and 5T4-PBD, an ADC composed of 5T4_0108 conjugated with SG3249, a DNA cross-linking PBD payload (27).…”
Section: Generation and In Vitro Characterization Of 5t4_0108 Antibodymentioning
confidence: 99%
“…However, the activity of cytotoxics can be context dependent, where certain classes of drugs are more effective than others depending on the type of cancer. Therefore, studies were conducted to determine the relative activity of 5T4-Tub and 5T4-PBD, an ADC composed of 5T4_0108 conjugated with SG3249, a DNA cross-linking PBD payload (27).…”
Section: Generation and In Vitro Characterization Of 5t4_0108 Antibodymentioning
confidence: 99%
“…Free SG3199 had an IC 50 of ~1 pM (Figure 3A, Table S1), this confirmed its toxicity towards trypanosomes and indicated that it is freely cell permeable. Prior to conjugation to the IgGs, SG3199 was modified by the addition of a linker to facilitate conjugation and release in the lysosome after proteolysis to produce SG3249(43) (Figure 1B). Free SG3249 had an IC 50 of ~240 pM (Figure 3A, Table S1); presumably the hydrophilic nature of the linker meant that cell access via passive diffusion was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…PBD dimers bind in the minor groove and cross-link specific repeat sequences in the DNA through the N10 position of both monomers. 24 Two of the PBD ADCs that are currently in clinical development (SGN-CD33A and Rova-T ADCs) use PBD linker-payloads, SGD-1910 and SG3249, respectively. 25,26 Like the PBD payload, the D211 payload has IC 50 values in the picomolar range in AML cell lines.…”
Section: Discussionmentioning
confidence: 99%